Bioactive Compounds in Herbal Bitter Drinks and Effects on selected Hepatic Biomarkers in Albino Wister Rats in Lagos, Nigeria - A.B. Ojekale; O. Lawal; M.O. Lasisi; C.A. Bamgbose; F.A. Dosu (Journal of Applied Sciences and Environmental Management)
Recently in Nigeria, the use of natural products described as herbal bitter drinks presumed to cure all except death has been on the increase. This paper therefore evaluates the bioactive compounds of three herbal drinks and their concomitant effects on selected hepatic biomarkers in albino Wister rats in Lagos, Nigeria using standard methods. A total of 31 bioactive compounds were positively identified in the three bitter drinks analyzed, Out of which are: Yoyo (5-Hydroxymethylfurfural (6.8%), Coumaran (1.7%), Octamethyl cyclotetrasiloxane ( 4.5%), Squalene(3.2%) - 2,4-Dihydroxy-2,5-dimethyl-3(2H)-furan-3-one(1.7%),3,3-Dimethyl-2butanol(1.1%),2-Hydroxy-2- cyclopenten-1-one (0.7%)). Swedish (Camphor (82.9%), Cinnamic acid (0.2%)). Living (5-Hydroxymethylfurfural 57.4%), Coumaran (1.6%), 3, 4-dihydroxy-3-cyclobutene-1, 2-dione (0.3%). The three bitters had no common bioactive compound between them. Five common bioactive compounds were detected present in both Living and Yoyo bitters. Only 11 (about 35%) of the 31 compounds  identified have established and documented pharmacological use. Some of the bioactive components in each of the bitters support the advertised usage of the formulations. The three bitters orally administered to rats from data gathered were not dangerous to the liver over the 40day period of the experiment.